Conductivity and FTIR studies on PEO- NaCF3SO3 solid polymer electrolyte films / Mohd Noor Zairi Mohd Sapri and Azizah Hanom Ahmad. - Mohd Sapri, Mohd Noor Zairi; Ahmad, Azizah Hanom (2016)
Solid polymer electrolytes electrolytes based Poly (ethylene oxide) (PEO) complexed with sodium trifluoromethanesulfonate (NaCF3SO3) salt were prepared by using solution cast technique. Ion-polymer ionic conductivity and interaction studies have been reported by Electrical Impedance spectroscopy (EIS) and Fourier transform infrared spectroscopy (FTIR). FTIR studies suggested that there are stronger interaction between Na+ ions and the polymer than interaction of anions cations of the salt. The temperature dependance electrical conductivity of polymer electrolytes films follow Arrhenius relation and the low activation energy 0.2993 eV was observed for PEO-18 wt. % NaCF3SO3 below 323 K.